Tailoring of optical band gap and electrical conductivity in a-axis oriented Ni doped Chromium Oxide thin films. Issue 10 (July 2018) - Shaukat, Saima; Khaleeq-ur-Rahman, M.; Ilyas, Usman; Naseem, Shahzad; Dildar, I.M.; Latif, A.; Rawat, R.S.
Abstract: Ni doped Cr2 O3 (NCO) films have attracted much attention due to their applications in the field of photovoltaics. This study reports the tailoring of structural, electrical and optical properties as a function of Ni doping in Chromium oxide (Cr2 O3 ). NCO thin films were grown by Pulsed laser deposition (PLD) using 2nd harmonic Nd:YAG Laser on n-Si (100) with in-situ annealing of 450 °C. Structural analyses based on X-ray diffractometry (XRD) and Raman Spectroscopy showed the inconsistent variation in crystallinity and shift in A 1 g band in turn revealing the successful incorporation of Ni into Chromium oxide host lattice. In addition, electrical measurements also showed an inconsistent variation in resistivity ranging from 10 2 to 10 4 Ω − cm . The properties showed widening of band gap energy (E g ) from 3.41 to 3.60 eV as a function of Ni doping concentration with significantly decreased reflectance in the range of 500–600 nm thereby increasing the absorption, a pre-requisite for solar absorbers. Highlights: Pulsed laser deposition (PLD) of undoped and Ni doped Cr2 O3 films onto n-Si (100). Rhombohedral Polycrystalline films grown with preferred orientation of (300) plane. Diffused grain growth of nanoparticles observed with smooth surface morphology. Red and blue shift of Raman A1 g mode confirmed the successful incorporation of Ni. Improved band gap with Ni doping, a pre-requisite for photovoltaics.